2009
DOI: 10.1200/jco.2008.18.2808
|View full text |Cite
|
Sign up to set email alerts
|

Ki67 Expression and Docetaxel Efficacy in Patients With Estrogen Receptor–Positive Breast Cancer

Abstract: PURPOSE The indications of adjuvant chemotherapy for patients with estrogen receptor (ER) -positive breast cancer are controversial. We analyzed the predictive value of Ki67, HER2, and progesterone receptor (PR) expression for the efficacy of docetaxel in patients with ER-positive, node-positive breast cancer. PATIENTS AND METHODS Expression of Ki67, HER2, and PR was measured by immunohistochemistry in tumor samples from 798 patients with ER-positive breast cancer who participated in PACS01, a randomized trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
141
2
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(160 citation statements)
references
References 22 publications
10
141
2
6
Order By: Relevance
“…In addition, , taxane yielded the therapeutic effect of RR; 28.3% and TTP; 8.3 months in luminal metastatic breast cancer. The results of the present analysis were not comparable to the numerous previous studies (6)(7)(8), which showed the ineffectiveness of taxane anticancer drugs for operable early luminal breast cancer. Possible causes of the difference in the results of pre-and postoperative taxane treatment for early breast cancer and those of taxane treatment for luminal metastatic breast cancer include the following factors.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In addition, , taxane yielded the therapeutic effect of RR; 28.3% and TTP; 8.3 months in luminal metastatic breast cancer. The results of the present analysis were not comparable to the numerous previous studies (6)(7)(8), which showed the ineffectiveness of taxane anticancer drugs for operable early luminal breast cancer. Possible causes of the difference in the results of pre-and postoperative taxane treatment for early breast cancer and those of taxane treatment for luminal metastatic breast cancer include the following factors.…”
Section: Discussioncontrasting
confidence: 54%
“…Accordingly, immunohistochemical classification with hormone receptors and human epidermal growth factor receptor 2 (HER2) may be used to estimate the subtype. Luminal A breast cancer was defined to express estrogen receptor (ER) and not express HER2 in the CALGGB 9344 trial (6), express ER and/or progesterone receptor (PgR) with a low Ki67 labeling index (cut-off, 13%) in the BCIRG 001 trial (7), and express ER with a low Ki67 labeling index (cut-off, 20%) in the PACS 01 trial (8). In addition, the St. Gallen International Conference 2011 proposed that breast cancer expressing ER and/or PgR, and negative for HER2 with a Ki67 labeling index of <14%, should be defined as luminal A breast cancer (9).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, many of the neoadjuvant and adjuvant chemotherapeutic interventions approved for clinical use include agents targeting either replicating cells (in S phase) or dividing cells (M phase), and will therefore only be effective against cells progressing through the cell cycle. In support of this concept, in breast cancer, high Ki67 levels appear to predict benefit for an adjuvant taxane regime (M phase agent docetaxel) compared with non-taxane regimes [104,105]. However, although Ki67 has emerged as a prognostic marker of potential interest, its introduction into routine clinical practice has been compromised by conflicting data from meta-analysis studies [106].…”
Section: Tumour Cell Cycle Phase Analysismentioning
confidence: 99%
“…Our previous study showed that patients whose breast tumors showed low Ki67 expression displayed longer time to progression during first-line endocrine therapy with aromatase inhibitors [21]. On the other hand, randomized clinical studies on adjuvant chemotherapy have retrospectively reviewed data and reported that Ki67 was a predictor of benefit from chemotherapy with endocrine therapy in ER-positive breast cancer [22][23][24]. Therefore, expression levels of Ki67 are involved in biological characteristics of the tumors, including prognosis and response to certain kinds of therapies in ER-positive breast cancer.…”
mentioning
confidence: 99%